Experimental Archaeometallurgy of Early-Middle Bronze Age Cyprus: Pilot Experiments of Copper Smelting at Pyrgos-Mavroraki - Marco Romeo Pitone (EXARC Journal, 2018)
Pyrgos-Mavroraki, an early 2nd millennium BC proto-industrial settlement, is an excellent case-study on which to apply experimental archaeometallurgy because it presents many different elements connected to the chaine-operatoire of copper metallurgy, typical of Early/Middle Bronze Age Cyprus. The site excavated by the Italian Archaeological Mission of the ITABC-CNR of Rome (Institute for Technologies applied to the Cultural Heritage of the Italian National Research Council), revealed different metallurgical areas and a coppersmith workshop equipped with a set of basalt anvils (Belgiorno, 2017). The combination of the metallurgical evidence of the entire copper processing (crucibles, moulds, anvils, stone tools), the huge presence of non-tapping slags all over the site and the identification of several structures interpretable as furnaces, suggested that some sort of smelting process took place at Pyrgos-Mavroraki. Some pilot experiments have been preliminarily carried out to test the construction technique, shape and thermal behaviour of the furnaces during a smelting process using different fuels. The simple, but important outcomes of these experiments will be essential to design an accurate protocol for the systematic experimental studies of the archaeometallurgy of this site (objective of a Northern Bridge Training Partnership funded PhD at Newcastle University).